The C825T Polymorphism of the G-Protein β3 Gene as a Risk Factor for Functional Dyspepsia: A Meta-Analysis - Yi-Zuo Song; He-Yi You; Zhe-Hui Zhu; Zheng-De Wen; Hui-Ying Xu; Bi-Cheng Chen; Zong-Jing Chen; Qing-Ke Huang (Gastroenterology Research and Practice)
Background. Functional dyspepsia (FD) is a functional upper gastrointestinal disorder with significant morbidity and medical costs. Previous studies investigated the association of G-protein β3 (GNB3) genetic polymorphisms with FD but with inconsistent results. Therefore, we performed a meta-analysis to derive a precise estimation of the relationship between GNB3 polymorphisms and FD. Methods. We searched different databases including PubMed, EMBASE, CNKI, and the Ovid Library to gather eligible studies on GNB3 polymorphisms and FD. The association was assessed by the odds ratio (OR) with 95% confidence intervals (CI). Results. We identified 12 studies with 1109 cases and 2853 controls for the analysis. We found no associations of GNB3 C825T polymorphism with FD in the overall population (T versus C, OR = 1.06, 95% CI: 0.96–1.18, P=0.26; TT versus CC + CT, OR = 1.16, 95% CI: 0.97–1.39, P=0.11; TT + CT versus CC, OR = 1.01, 95% CI: 0.77–1.31, P=0.96; TT versus CC, OR = 1.15, 95% CI: 0.93–1.44, P=0.20). Subgroup analyses by genotyping method indicated that the magnitude of association was strengthened for additive model (OR = 1.15, 95% CI: 1.07–2.24, P=0.02). Sensitivity analysis did not reveal significant associations under all models. Conclusions. This meta-analysis demonstrates that GNB3 C825T polymorphism may not be a risk factor for FD.